The Effect of the Reading Speed Method on the Level of Comprehension of Story Reading Content in the Indonesian Language Subject for Grade V Students of SDN Landah - Made Ayu Pransisca; Munawir Gazali; Syaipul Pahru (Lembaga Bale Literasi, 2026)
This study aims to find out the difference in learning outcomes between students who use the Reading Speed method. This study uses a quantitative approach with an experimental type. The population in this study is 41 students in grade V of SDN Landah. Meanwhile, the sampling used is a simple random sampling technique. The class that became a sample was class V A as an experimental class that used the Reading Speed method and V B as a control class that used a conventional learning model. This research instrument is in the form of a test. The research design used is a true experimental posttest only control design. The data analysis technique uses a t-polled variance test. The results showed that there was a difference in the average learning outcomes between students who used the Reading Speed method and students who used the conventional learning model. This is evidenced by the results of the hypothesis test, namely the tcount > ttable where 5.25 > 2.019 which means that H0 is rejected and Ha is accepted.